Whey peptides exacerbate body weight gain and perturb systemic glucose and tissue lipid metabolism in male high-fat fed mice. Issue 8 (29th March 2021) - D'Souza, Kenneth; Acquah, Caleb; Mercer, Angella; Paudel, Yadab; Pulinilkunnil, Thomas; Udenigwe, Chibuike C.; Kienesberger, Petra C.
Abstract : Consumption of milk-derived whey proteins has been demonstrated to have insulin-sensitizing effects in mice and humans, in part through the generation of bioactive whey peptides. Abstract : Consumption of milk-derived whey proteins has been demonstrated to have insulin-sensitizing effects in mice and humans, in part through the generation of bioactive whey peptides. While whey peptides can prevent insulin resistance in vitro, it is unclear whether consumption of whey peptides can prevent obesity-induced metabolic dysfunction in vivo . We sought to determine whether whey peptides consumption can protect from high fat (HF) diet-induced obesity and dysregulation of glucose homeostasis. Male C57BL/6J mice were fed either a low or HF diet for 13 weeks. HF diet fed mice were provided drinking water with no addition (control), undigested whey protein isolate (WPI, 1 mg ml −1 ) or whey protein hydrolysate (WPH, 1 mg ml −1 ) throughout the diet regimen. Mice consuming WPH gained more body weight and were more glucose intolerant compared to those consuming WPI or water only. Despite increased body weight gain, perigonadal adipose tissue weight and lipid accumulation were unchanged. However, excess lipids accumulated ectopically in the liver and skeletal muscle in mice consuming WPH, which was associated with elevated inflammatory markers systemically and in adipose tissue, liver, and skeletal muscle. In skeletal muscle, mitochondrial fat oxidation and electron transport chain proteins were decreased with WPH consumption, indicative of mitochondrial dysfunction. Taken together, our results demonstrate that WPH, but not WPI, exacerbates HF-induced body weight gain and impairs glucose homeostasis, which is accompanied by increased inflammation, ectopic fat accumulation and mitochondrial dysfunction. Thus, our results argue against the use of dietary whey peptide supplementation as a preventative option against HF diet-induced metabolic dysfunction.